Analisis Risiko Kegagalan Mesin Thresher Menggunakan Metode Failure Mode and Effect Analysis (FMEA) dan Risk Priority Number (RPN) di Pabrik Kelapa Sawit PT. MAS - Ahmad Khoirul Humam Nazhif; Harwadi Harwadi; Indra Feriadi (Jurnal Inovasi Teknologi Terapan, 2026)
The thresher machine plays a critical role in separating palm fruits from bunches in palm oil mills. Failures in the thresher machine can lead to increased downtime, production losses, and reduced Crude Palm Oil (CPO) output. This study aims to identify potential failure modes of the thresher machine and determine the most critical components using Failure Mode and Effect Analysis (FMEA) and Risk Priority Number (RPN). This research employs a quantitative descriptive approach with a case study conducted at PT. MAS Palm Oil Mill from January to December 2024. Data were collected through field observations, structured interviews, and operational record analysis. The results show that the thresher machine operated for 5,384 hours with a total downtime of 37 hours due to 11 failure events. Based on the RPN calculation, the V-belt has the highest risk level with an RPN value of 128, followed by the spider component with an RPN value of 126. These components are identified as critical and should be prioritized in maintenance planning. The implementation of FMEA and RPN can support effective maintenance decision-making, reduce downtime, and improve the reliability of the thresher machine.